Deglaciation and future stability of the Coats Land ice margin, Antarctica - D. A. Hodgson; D. A. Hodgson; K. Hogan; J. M. Smith; J. A. Smith; C.-D. Hillenbrand; A. G. C. Graham; P. Fretwell; C. Allen; V. Peck; J.-E. Arndt; B. Dorschel; et al. (The Cryosphere, 2018)
The East Antarctic Ice Sheet discharges into the Weddell Sea via the Coats Land ice margin. We have used geophysical data to determine the changing ice-sheet configuration in this region through its last glacial advance and Holocene retreat and to identify constraints on its future stability. Methods included high-resolution multibeam bathymetry, sub-bottom profiles, seismic-reflection profiles, sediment core analysis and satellite altimetry. These provide evidence that Coats Land glaciers and ice streams merged with the palaeo-Filchner Ice Stream during the last glacial advance. Retreat of this ice stream from 12 848 to 8351 cal. yr BP resulted in its progressive southwards decoupling from Coats Land outlet glaciers. Moraines and grounding-zone wedges document the subsequent retreat and thinning of these glaciers, their loss of contact with the bed and the formation of ice shelves, which re-advanced to pinning points on topographic highs at the distal end of the troughs. Once fully detached from the bed, these ice shelves were predisposed to rapid retreat back to coastal grounding lines. This was due to reverse-bed slopes, the consequent absence of further pinning points in the troughs and potentially to the loss of structural integrity resulting from weaknesses inherited at the grounding line. These processes explain why there are no large ice shelves in the eastern Weddell Sea between 75.5 and 77° S.